(177)Lu-labelled macrocyclic bisphosphonates for targeting bone metastasis in cancer treatment - Bergmann, Ralf; Meckel, Marian; Kubíček, Vojtěch; Pietzsch, Jens; Steinbach, Jörg; Hermann, Petr; Rösch, Frank (EJNMMI research, 2016)
BACKGROUND: Metastatic bone lesion is a common syndrome of many cancer diseases in an advanced state. The major symptom is severe pain, spinal cord compression, and pathological fracture, associated with an obvious morbidity. Common treatments including systemic application of bisphosphonate drugs aim on pain reduction and on improving the quality of life of the patient. Particularly, patients with multiple metastatic lesions benefit from bone-targeting therapeutic radiopharmaceuticals. Agents utilizing beta-emitting radionuclides in routine clinical praxis are, for example, [(89)Sr]SrCl2 and [(153)Sm]Sm-EDTMP. No-carrier-added (n.c.a.) (177)Lu is remarkably suitable for an application in this scope. METHODS: Five 1,4,7,10-tetraazacyclododecane N,N',N'',N''-tetra-acetic acid (DOTA)- and DO2A-based bisphosphonates, including monomeric and dimeric structures and one 1,4,7-triazacyclononane-1,4-diacetic acid (NO2A) derivative, were synthesized and labelled with n.c.a. (177)Lu. Radio-TLC and high-performance liquid chromatography (HPLC) methods were successfully established for determining radiochemical yields and for quality control. Their binding to hydroxyapatite was measured in vitro. Ex vivo biodistribution experiments and dynamic in vivo single photon computed tomography (SPECT)/CT measurements were performed in healthy rats for 5 min and 1 h periods. Data on %ID/g or standard uptake value (SUV) for femur, blood, and soft-tissue organs were analyzed and compared with [(177)Lu]citrate. RESULTS: Radiolabelling yields for [(177)Lu]Lu-DOTA and [(177)Lu]Lu-NO2A monomeric bisphosphonate complexes were >98 % within 15 min. The dimeric macrocyclic bisphosphonates showed a decelerated labelling kinetics, reaching a plateau after 30 min of 60 to 90 % radiolabelling yields. All (177)Lu-bisphosphonate complexes showed exclusive accumulation in the skeleton. Blood clearance and renal elimination were fast. SUV data (all for 1 h p.i.) in the femur ranged from 3.34 to 5.67. The bone/blood ratios were between 3.6 and 135.6, correspondingly. (177)Lu-bisphosphonate dimers showed a slightly higher bone accumulation (SUVfemur = 4.48 ± 0.38 for [(177)Lu]Lu-DO2A(P(BP))2; SUVfemur = 5.41 ± 0.46 for [(177)Lu]Lu-DOTA(M(BP))2) but a slower blood clearance (SUVblood = 1.25 ± 0.09 for [(177)Lu]Lu-DO2A(P(BP))2; SUVblood = 1.43 ± 0.32 for [(177)Lu]Lu-DOTA(M(BP))2). CONCLUSIONS: Lu-complexes of macrocyclic bisphosphonates might become options for the therapy of skeletal metastases in the near future, since they show high uptake in bone together with a very low soft-tissue accumulation.
Keywords: Biodistribution; Bisphosphonate; Theranostics; Bone metastases; DOTA; 177Lu; DO2A